OPTIMIZATION OF SYNTHESIS CONDITIONS OF lead-barium titanate-zirconate COMPOSITES CONTAINING METAL ATOMS AND THEIR DIELECTRIC PROPERTIES - L. I. Gurskii; J. .. Macutkevic; M. N. Saraseko; A. G. Poddubskaya; A. V. Petrov; N. A. Kalanda; A. A. Klimsa; O. V. Ignatenko; P. N. Kireev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Composition materials on the base of Pb0,75Ba0,15Zr0,53Ti0,47O3 (PBZT) with micro-inclusions of Cu and Ni are prepared by a complex ceramic technology. This technology includes metallization procedures by means of the chemical deposition method from standard solutions of nickel and copper. At determination of correlation of the structure of PBZT composites and their dielectric properties it was shown that dielectric losses increase with decreasing temperature. This is caused by the domination of the real part of the complex dielectric permittivity.